Longer time after bariatric surgery and sedentary leisure modify anthropometric parameters, body composition and sarcopenic obesity markers in women - Luzia Hintze; Danilo Silva; Josiane Bianchini; Rafaela Dada; Jessica McNeil; Nelson Nardo Junior (Revista Brasileira de Atividade Física e Saúde)
Sarcopenic Obesity is known as a decrease in the quantity and quality of the skeletal muscle mass and increase in fat mass. It can be measured by the residual appendicular skeletal muscle mass (Ap SMM) based on the difference between actual and predicted values. Even though this condition is more common among sedentary elderlies, it may be present in subjects who underwent Bariatric Surgery (BS). We aimed to evaluate the influence of time after BS and physical activity level (PAL) during leisure time on anthropometric parameters, body composition and sarcopenic obesity markers in women. It is a cross-sectional study involving 42 women divided into two groups according to the time since BS and two groups according to PAL. Anthropometric variables, body composition, and sarcopenic obesity markers were assessed. The variables appendicular skeletal muscle mass, height, and fat mass were used to determine sarcopenic obesity markers. Non-parametric numerical tests were used for group comparison and significance level was set at p<0.05. Considering women with sedentary leisure only, those with longer time after BS had higher current body weight and BMI, waist and hip circumference, fat mass, fat-free mass, Ap SMM (equation, residual, and relative) (p<0.05). Considering women with longer time after BS only, sedentary ones had higher current body weight and BMI, waist circumference, fat mass, fat-free mass (relative only), Ap SMM (equation and relative) (p<0.05). Our data indicate that longer time after BS and sedentary leisure modify anthropometric parameters, body composition and sarcopenic obesity markers in women.